Republic of Kosovo : Staff Report for the First Assessment Under the Staff-Monitoring Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper presents the first assessment report under the Staff-Monitored Program (SMP) for Kosovo. The policies under Kosovo's SMP target decisive steps toward fiscal sustainability and stronger budget management and execution. Performance under the SMP has been largely satisfactory to date, with all end-September benchmarks but one having been met. The end-September structural benchmark on the formulation of a tax compliance strategy was also met. A budget for 2012 was submitted to the Assembly at end-October that is in line with the authorities' commitments under the SMP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet